SEX AND RELIGION: Contemporary Responses - Chackalackal, Saju (Journal of Dharma, 2009)
The fact that human societies from the beginning had a normative approach to everything related to sex and sexuality is indisputable, whether its source was religion or state, or the ‘private’ conscience of an individual. It is also a fact that most of it has been evolving and changing over time. Although there had been continued and consistent attempts on the part of the libertines to ridicule and challenge the norms that were in place, they have not yet succeeded in overthrowing normative approaches to sexuality altogether, which, I think, is the case also with the most ‘liberated’ crusades of free sex. Yet, interestingly, we must also be open enough to admit the fact that despite all these norms, average human sexual behaviour (if we could go by the ‘scientifically’ conducted survey results that are made available to us in our present times) very seldom fits into the normative moulds, especially when it comes to the private lives of many individuals. It is also true that moral or legal norms with regard to sexual behaviour, to some extent, have tended to inflict people with a burdensome conscience, either of sin or of guilt, which is said to have resulted in enslaving them than ultimately facilitating a liberating experience that both religion and state are expected to provide. Then, does it amount to saying that there is no point in having moral norms with regard to the sexual behaviour of human individuals and societies? In this context, it is important to ask the simple question, why should there be norms – moral and/or legal – in the sphere of human sexual behaviour?